Case Report: Papillophlebitis associated with MOG-IgG-associated optic neuritis - Dai, Yuanmin; Zhang, Siran; Lou, Yue (Frontiers in Medicine, 2025)
Optic neuritis is a common manifestation in patients with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). However, its association with papillophlebitis is rare and has only been sporadically reported in the literature. Papillophlebitis is primarily characterized by central retinal vein occlusion (CRVO) and typically affects young to middle-aged adults. We present the case of a 27-year-old woman who initially presented to the emergency department with headache, fever, and seizures. During her hospitalization, MOGAD was diagnosed based on brain MRI, cerebrospinal fluid analysis, and serological testing. Following the initiation of systemic corticosteroid therapy, bilateral optic neuritis was observed. One month later, the patient reported decreased vision in her left eye. Multimodal retinal imaging revealed tortuous retinal veins, flame-shaped hemorrhages, macular edema, and mild leakage from the optic disk and retinal vessels on fluorescein angiography (FA). Genetic testing identified homozygous MTHFR (C665T) and heterozygous PAI-1 (4G/5G) mutations, which supported the diagnosis of papillophlebitis. The patient’s vision improved following intravitreal anti-VEGF therapy. To the best of our knowledge, this is the first reported case of papillophlebitis occurring as a secondary complication of MOG-associated optic neuritis. This finding provides new insight into the spectrum of MOGAD and underscores the importance of regular fundus examinations during treatment to facilitate the timely management of ocular complications.